Artificial Intelligence Development on “Golem” Non-Playable Character in Miner Quest Games With Finite State Machine Method - Zikri, Afdhal (Universitas Telkom, 2024)
Digital educative game is an example of technology currently often used by kindergarten teachers to make topics or subjects easier for students to understand. By using the function of digital educational games, researchers plan to develop a